Dramatic response of refractory sarcoidosis under ruxolitinib in a patient with associated JAK2-mutated polycythemia. Issue 6 (20th December 2018) - Rotenberg, Cécile; Besnard, Valérie; Brillet, Pierre-Yves; Giraudier, Stéphane; Nunes, Hilario; Valeyre, Dominique
Sarcoidosis is a systemic disorder of unknown aetiology characterised by the formation of non-caseating epithelioid granulomas in involved organs. Although a spontaneous remission is frequent, up to 28–53% of patients may follow a persistent active course for more than 5 years [1, 2]. Outcome may be severe in a subset of these patients. Sarcoidosis treatment relies on three lines of therapies respectively corticosteroids, immunosuppressive medications and anti-tumour necrosis factor-α (anti-TNF-α) therapy according to severity. Potential role of the JAK-STAT pathway in sarcoidosis http://ow.ly/L8Du30m78XI